On the Origin of Dark Current in Organic Photodiodes. Issue 1 (11th November 2019) - Simone, Giulio; Dyson, Matthew J.; Weijtens, Christ H. L.; Meskers, Stefan C. J.; Coehoorn, Reinder; Janssen, René A. J.; Gelinck, Gerwin H.
Abstract: Minimizing the reverse bias dark current while retaining external quantum efficiency is crucial if the light detection sensitivity of organic photodiodes (OPDs) is to compete with inorganic photodetectors. However, a quantitative relationship between the magnitude of the dark current density under reverse bias (   J d ) and the properties of the bulk heterojunction (BHJ) active layer has so far not been established. Here, a systematic analysis of J d in state‐of‐the‐art BHJ OPDs using five polymers with a range of energy levels and charge transport characteristics is presented. The magnitude and activation energy of J d are explained using a model that assumes charge injection from the metal contacts into an energetically disordered semiconductor. By relating J d to material parameters, insights into the origin of J d are obtained that enable the future selection of successful OPD materials. Abstract : The reverse bias dark current density in organic bulk heterojunction photodiodes and its activation energy are measured and successfully reproduced in terms of thermal charge injection from the contacts into a broadened density of states at the interface. The agreement is excellent for five polymer semiconductors with widely varying energy levels and charge transport characteristics.